How the U.S. capital markets volatility interacts with economic growth - Curto, J.; Marques, J (Annals of Economics and Finance, 2013)
Empirical finance suggests that US capital markets' volatility has a negative relationship with economic growth. As the main focus is on the equity market volatility dynamics and less on other equally important asset types, in this paper we examine the dynamics between US money markets, government debt, corporate debt and equities volatilities, and a real GDP growth proxy, between 1963 and 2009. Results show that assets' volatility is essentially counter-cyclical of growth. However, this interaction changes when specific time subsamples are considered: in recessions, rising volatility leads the economic cycle, while in expansions its downward trend lags the business cycle.